Comparison of colposcopic biopsy results of cervical cytology-negative and HPV 16/18 or other high-risk HPV subtypes (Annals of Medical Research, 2021)
Aim: This study aimed to compare the colposcopic biopsy results of patients with negative cervical cytology and positive human papillomavirus (HPV) tests and to investigate the necessity of colposcopy in patients with cytology-negative/other high-risk HPV (non-HPV 16/18) positive results.Materials and Methods: The study included 126 patients aged 30–65 years who underwent HPV DNA testing between 2016 and 2019 and who underwent colposcopic biopsy at our hospital because of their positive results. The patients were divided into three groups: HPV16/18 positivity, other high-risk HPV positivity, and unclassified HPV positivity. Cytology and colposcopy-guided cervical biopsy results were compared with the HPV types.Results: Approximately 44.4% of the patients had HPV 16/18 positivity, 23% had other high-risk HPV positivity, and 32.5% had unclassified HPV positivity. The cytology results revealed that 57.1% of patients were negative for intraepithelial lesions or malignancy (NILM), 22.2% had atypical squamous cells of undetermined significance, 17.5% had low-grade squamous intraepithelial lesions (LGSIL), and 2.4% had high-grade squamous intraepithelial lesions. Colposcopic biopsy results were normal in 15.1% of the patients, showed LGSIL in 15.9%, high-grade squamous intraepithelial lesions (HGSIL) in 10.3%, and cervical cancer in 0.8% of the patients. Evaluation of the biopsy results based on HPV type in the patients with NILM cytology revealed that 12.8% of those with HPV 16/18 positivity had LGSIL and 17.9% had HGSIL, whereas 7.1% of those with other high-risk HPV positivity had HGSIL and 7.1% had LGSIL. Conclusions: The possibility of detecting dysplasia in the colposcopic biopsies of patients who are NILM and HPV 16/18-positive is higher than in the colposcopic biopsies of patients with other high-risk HPV types; therefore, these patients should be evaluated using colposcopic biopsy. Colposcopic biopsy is unnecessary in the presence of NILM and other high-risk HPV types.